Economics - Solmon, Lewis C. (Reading, Mass. : Addison-Wesley Pub. Co., 1976)
In this second edition, the text is designed for use as introductory economics courses at the college level. It includes systematic and comprehensive coverage of basic concept and principles, elucidations of the necessary terminology, and applications of the concepts and principles to the multitude of economics problems in our modern world.
Includes index.
Includes bibliographical references: p. 772-784.
aia 13/11/2017
Loans
Keywords: Economics